Atitrauktinio kirčio priegaidės šiaurės žemaičių kretingiškių tarmėje - Babickienė, Zofija (Baltistica, 2005)
ON THE RETRACTED SYLLABLE ACCENT IN THE NORTH-ŽEMAITIAN DIALECT OF KRETINGA There are different opinions about the retracted syllable accent in the Lithuanian dialects. The purpose of this paper is to describe the prosodic features of the retracted syllable accent in the North-Žemaitian dialect of Kretinga in more detail. It is important because of the following two main reasons: the area of the retracted syllable accent tends to be described as being much smaller in traditional Lithuanian dialectology; and the tendency of the retracted syllable accent to be levelled in the present dialect of the North-Žemaitian dialect of Kretinga. The research was carried out with the help of a computer-based programme PRAAT 4.0.45, and the results were evaluated statistically. The results of the investigation show that retracted syllable accents obviously differ not only in the area of Mosėdis-Salantai but also quite far from those areas, viz. in fact in all the areas of the North-Žemaitian dialect of Kretinga. The research demonstrates that the acute and circumflex retracted syllable accents in the North-Žemaitian dialect of Kretinga differ mainly in fundamental frequency and intensity.